Copper Sulfide Nanoparticles-Incorporated Hyaluronic Acid Injectable Hydrogel With Enhanced Angiogenesis to Promote Wound Healing - Zhou, Wencheng; Zi, Liu; Cen, Ying; You, Chao; Tian, Meng (Frontiers in Bioengineering and Biotechnology, 2020)
Skin wound caused by trauma, inflammation, surgery, or burns remains a great challenge worldwide since there is no effective therapy available to improve its clinical outcomes. Herein, we report a copper sulfide nanoparticles-incorporated hyaluronic acid (CuS/HA) injectable hydrogel with enhanced angiogenesis to promote wound healing. The prepared hydrogel could not only be injected to the wound site but also exhibited good photothermal effect, with temperature increasing to 50 °C from room temperature after 10 min of near-infrared light irradiation. The cell culture experiments also showed that the hydrogel has no cytotoxicity. In the rat skin wound model, the hydrogel treated wounds exhibited better healing performances. Masson’s trichrome staining suggested that collagen deposition in wounds treated with the hydrogel was significantly higher than other groups. The immunohistochemical staining showed that the hydrogel can effectively upregulate the expression of vascular endothelial growth factor (VEGF) in the wound area at the incipient stage of healing, and the CD 31 immunofluorescence staining confirmed the enhanced angiogenesis of the hydrogel. Taken together, the prepared CuS/HA hydrogel can effectively increase the collagen deposition, upregulate the expression of VEGF, and enhance the angiogenesis, which may contribute to promote wound healing, making it a promising for application in treating skin wound.